American Women of the Colonial Period and of the Nineteenth Century City: in Judith Sargent Murray’s On the Equality of Sexes, Edith Wharton’s Roman Fever and Hamlin Garland’s Mrs. Ripley‘s Trip - Khelifa Arezki; Katia Mahmoudi (Multilinguales)
The aim of the present paper is to shed light on women’s condition within the American society during the colonial period and the 19th century. The study will center on the gendered place that women were forced to take, and on the male constructed stereotypes to which they were subjected from an Enlightenment liberal Feminist perspective. We will bring into awareness how a woman was obliged to obey social constructed prejudices which made of her an object; all opportunities for education, prospect, liberation and development were closed to her.